Pengaruh Kompetensi Sumber Daya Manusia Dan Pemanfaatan Teknologi Informasi Terhadap Laporan Keuangan Berbasis Akrual - Samukri Samukri; Ananda Sukma Pratiwi; Ramdany Ramdany (Jurnal Ilmiah Akuntansi Kesatuan, 2021)
This study aims to examine the effect of thin capitalization, capital intensity and institutional ownership on tax avoidance. The dependent variable used is tax avoidance, and the independent variables used are thin capitalization, capital intensity and institutional ownership. The subjects of this research are manufacturing companies in the food and beverage sub-consumer goods industry sector listed on the 20 The accrual basis is a new thing for accounting in government, after several decades of use the cash basis. The recording of non-tax state receivables and revenues (PNBP) that is not in accordance with the Government Accounting Standards is a phenomenon of this research. In addition, the lack of use of information technology also affects it. This study aims to determine whether there is an influence and how much influence on human resource competence and the use of information technology in the application of the accrual basis to financial statements. This study uses 80 primary data taken from a survey of financial management staff in echelon 1. The data is processed using SPSS so that it can be seen that human resource competence has no significant effect, while the use of information technology has a significant effect on the application of the accrual basis to financial statements. Keywords: Human Resource Competence S, Use Of Information Technology, Cash basis, Accrual Basis, Financial Statements17-2019 BEI. This sample was selected using a purposive sampling method. The total sample used is 20 sample data. This research method uses multiple linear regression analysis which is processed using spss 25. The results of this study partially show that thin capitalization and institutional ownership have a positive and significant effect, while capital intensity has a negative and significant effect on tax avoidance. Meanwhile, it simultaneously shows that thin capitalization, capital intensity and institutional ownership have an effect on tax avoidance. Based on the results of the determination test which shows the value of the coefficient of determination is 31.1%. These results indicate the ability of the independent variable to explain the dependent variable by 31.1%, while the remaining 68.9% is explained by other variables. Keywords: Thin Capitalization, Capital Intensity, Institutional Ownership and Tax Avoidance